Incidence of Cervical Cancer in Young Adult Women: Level of Knowledge for its Prevention - Edison Sotalin Nivela; José Sixto Calvopiña del Castillo; Carlos Alberto Llerena Gómez (Revista Finlay)
Foundation: knowledge about cervical cancer helps women understand their personal risk and the importance of taking preventive measures. Objective: determine knowledge about the prevention and incidence of cervical cancer in young adult women. Methods: a descriptive, quantitative and correlational study was carried out on a sample selected under the criteria of nationality and age range. Data were collected through an online survey of 476 women aged 21 to 44 years. The sample corresponded to the universe. A purpose-built questionnaire was used to assess knowledge about cervical cancer. An electronic version of the questionnaire was created using Google Forms and published on the social networks Facebook and LinkedIn. The analysis of the data collected was carried out with descriptive statistical methods and the application of the Pearson chi-square test to calculate the correlations between the variables. The level of significance was taken as p < 0,05. Results: the knowledge of the women surveyed about the prevention and incidence of cervical cancer does not reach a sufficient level. No significant correlation was observed between knowledge and place of residence, economic situation, family history of cervical cancer, center where the cytological examination was performed, use of contraceptives, smoking or vaccination against human papillomavirus. It was found that knowledge was related to age, education, occupation, marital status, frequency of gynecological examinations, frequency of cytology, awareness of one's knowledge and the number of births. Conclusions: despite unlimited access to information, there are still many women who do not go to the gynecologist, do not have cytology and do not know how the Cervical Cancer Prevention and Early Detection Program works in Ecuador.